Acquisition of invasive traits in ant, Crematogaster subdentata mayr (Hymenoptera: Formicidae) in urban environments - Stukalyuk, Stanislav; Radchenko, Alexander; Akhmedov, Ascar; Reshetov, Alexander; Netsvetov, Maksym (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The native (primary) range of Crematogaster subdentata Mayr lies in Central Asia. Within the secondary range in Ukraine and Russia, it is invasive. The 1st objective of this work was to study the evolution of the biological and ecological features (habitats, queen number, colony structure, behavior, worker’s activity on foraging trails) of C. subdentata in the urban environments (Tashkent) and secondary ranges (Crimea, Rostov-On-Don region). Whilst, the 2nd objective was to compared these parameters in the natural habitats in the native (Uzbekistan) range. Result showed that in the territory of the primary range in Kyzylkum, colonies of C. subdentata are strictly monogynous; in Zarafshan’s oasis (riparian forests) they were polygynous (5.0±1.2 queens), but in cities of Uzbekistan C. subdentata forms supercolonies with hundreds of nests, and in total with hundreds of queens (on average 17.7±4.4 queens per one nest in supercolony). In the secondary range, C. subdentata forms even larger supercolonies with thousands of nests, containing 53.0±8.7 queens per nest. C. subdentata avoids contacts with another invasive ant species, Lasius neglectus, in the foraging territories both in the primary and secondary ranges, but other ant species avoid C. subdentata. Workers of C. subdentata are aggressive toward conspecific ones from other nests in the natural habitats, but are tolerance to those in both the secondary range and in the cities in the primary range. In conclusion, our results show that some ants may acquire invasive species traits in the urban habitats in the primary range.